2016
DOI: 10.1074/mcp.m115.054056
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Branch-specific Regulation of the Unfolded Protein Response by Nonsense-mediated mRNA Decay

Abstract: Nonsense-mediated mRNA decay (NMD) has originally been described as a surveillance mechanism to inhibit the expression of mRNAs with truncated open reading frames (ORFs) and to contribute to the fidelity of gene expression. It is now recognized that NMD also controls the expression of physiological genes with "intact" mRNA. Stress can decrease NMD efficiency and thus increase the mRNA levels of physiological NMD targets. As stress can also inhibit translation, the net outcome for shaping the proteome is diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
5
29
0
Order By: Relevance
“…This study moreover provided evidence that NMD plays a role in the timely termination of the UPR and therewith might protect cells from ER stress‐induced apoptosis . These findings are supported by a very recent paper showing that inhibition of NMD increases protein synthesis of downstream targets of the IRE1 and PERK pathways, suggesting a positive feedback loop in which ER stress dampens NMD, which in turn promotes the ER stress response …”
Section: Biological Functions Of Nmdsupporting
confidence: 77%
“…This study moreover provided evidence that NMD plays a role in the timely termination of the UPR and therewith might protect cells from ER stress‐induced apoptosis . These findings are supported by a very recent paper showing that inhibition of NMD increases protein synthesis of downstream targets of the IRE1 and PERK pathways, suggesting a positive feedback loop in which ER stress dampens NMD, which in turn promotes the ER stress response …”
Section: Biological Functions Of Nmdsupporting
confidence: 77%
“…He found that NMD suppression did not elicit detectable activation of either the PERK or IRE1α branches of the UPR pathway in U2OS and HeLa cells. Another study conducted in HeLa cells came to the same conclusion [73], as did a study performed in C2C12 myoblast cells [76]. In addition, Karam et al .…”
Section: Nmd and Stress Responses In Mammalsmentioning
confidence: 61%
“…The ability of NMD to target UPR component genes was confirmed recently by a proteomic study conducted by Sieber et al [73]. Through Pulse-SILAC and click-chemistry, these investigators found that several UPR proteins induced by the stressor, Dithiothreitol, were also upregulated in response to UPF1 depletion.…”
Section: Nmd and Stress Responses In Mammalsmentioning
confidence: 80%
“…NMD is a surveillance pathway that exists in all eukaryotes [31], [32]. It targets mRNAs harboring PTCs for degradation [33], which if left intact, would lead to production of truncated proteins with predicted deleterious effects for the organism [34]. From a medical view, this suggests that the NMD pathway plays a significant role in modulating the phenotypic outcome of genetic disorders that are caused due to the presence of PTC [35], [36].
Fig.
…”
Section: Discussionmentioning
confidence: 99%